2004
DOI: 10.1081/jas-200027983
|View full text |Cite
|
Sign up to set email alerts
|

Teaching School Teachers to Recognize Respiratory Distress in Asthmatic Children

Abstract: Using video footage, school teachers can be taught to visually recognize respiratory distress in asthmatic children. Improvement in visual recognition of respiratory distress was greater than improvement in didactic asthma information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
0
21
1
1
Order By: Relevance
“…Teacher knowledge, while equal to or higher than knowledge levels reported in previous studies (16-19, 31, 32), was still somewhat limited in some areas. The vast majority knew that dust, airborne irritants, changes in weather, animals with fur, colds and the flu, and mold were asthma triggers, and recognized that wheeze and shortness of breath were symptoms of asthma.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Teacher knowledge, while equal to or higher than knowledge levels reported in previous studies (16-19, 31, 32), was still somewhat limited in some areas. The vast majority knew that dust, airborne irritants, changes in weather, animals with fur, colds and the flu, and mold were asthma triggers, and recognized that wheeze and shortness of breath were symptoms of asthma.…”
Section: Discussioncontrasting
confidence: 74%
“…While teachers have many responsibilities and thus have limited time for non-academic tasks, interventions lasting only a few hours have greatly improved teacher knowledge (31, 32). Educating teachers about asthma may assist them to take prevention steps and may give them the confidence to react appropriately when symptoms occur.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that teachers can be effectively educated about how to identify asthma symptoms using didactic means or video instruction. [31] Additionally, an assessment tool of teacher efficacy and confidence level with regard to managing a child’s asthma at school [32] could be helpful in tracking teacher progress and contribute to development of asthma-friendly environment. Our findings will inform the design of an intervention focused on addressing the identified barriers and improving in-school asthma management in concordance with national standards.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have demonstrated schoolteachers' overall lack of knowledge of CPR and lack of confidence to manage asthma and epilepsy, Barrett 20 has illustrated the value of school nurses educating schoolteachers about emergencies in children. Sapien et al 21 demonstrated that schoolteachers' confidence level in recognizing respiratory distress in asthmatic children and knowledge of asthma medications improved after attending an education session consisting of video footage and didactic teaching.…”
Section: E742mentioning
confidence: 99%